The Effect of Transfer of Learning of Overhead Passing and Shooting Skills in Handball on the Achievement of Distance in the Javelin Throwing Event - Elkailani , Ghazi "Mohd Khair" (Dirasat: Educational Sciences, 2023)
Objectives: This study investigates the impact of applying handball's overhead passing and shooting skills to enhance javelin throwing distance and assesses the positive effects of this learning transfer. Methods: To achieve this, the researcher used the experimental approach on a sample of (35) students enrolled in the Handball and Athletics (2) course in the academic year 2020/2021. They were divided into two groups, an experimental (n = 17) and a control group (n = 18). After conducting the pre-measurement of the achievement distance in the javelin throwing event, the experimental group was taught the overhand passing and shooting skills; then, the two groups were taught the javelin throwing skills. To analyze the data of the study sample, the means, standard deviations, coefficient of variation, coefficient of torsion, and t-test of independent samples were used to indicate the differences between the post values of the two groups. Results: The study results showed that the achievement distance means in the post values for the control group was (12.14 m) and (17.13 m) for the experimental group. Additionally, there are differences in the achievement distance between the two groups, according to the variable of transferring the effect of learning, in favor of the experimental group, at a rate of (41.10%) using exact measurement and (17.04%) using balanced measurement. Conclusions: Based on the study's results, the researcher recommends the need to consider arranging the courses taught by the student so that they serve each other (horizontal transfer of the learning effect).